109k views
0 votes
Complete the steps to solve the equation. 3x - 6(5x + 3) = 9x + 6 1. The distributive property 3x - 30x 18 = gr + 6 2 Combine like terms. -27x - 18 = 9x + 6 3. Addition property of equality: -18 = 36x + 6 4. Subtraction property of equality: -24 = 36x 5. Division property of equality I​

User RVN
by
5.5k points

2 Answers

7 votes

Answer:


\small \sf x = (2)/(-3) \\

Explanation:

3x - 6(5x + 3) = 9x + 6.

Use the distributive property to multiply -6 by 5x + 3.

3x - 30x - 18 = 9x + 6

Combine 3x and -30x to get -27x.

-27x - 18 = 9x + 6

Subtract 9x from both sides.

-27x - 9x - 18 = 9x - 9x + 6

-36x - 18 = 6

Add 18 to both sides.

-36x - 18 + 18 = 6 + 18

-36x = 24

Divide both sides by -36.


\small \sf ( -36x)/( -36) = (24)/(-36) \\

Reduce the fraction
(24)/(-36) to lowest terms by extracting and canceling out 12.


\small \sf x = (2)/(-3) \\

User Sjay
by
6.2k points
4 votes

Answer:

see below

Explanation:

3x - 6(5x + 3) = 9x + 6

Distribute

3x -30x-18 = 9x+6

Combine like terms

-27x - 18 = 9x+6

Add 27x to each side

-27x+27x-18 = 9x+27x+6

-18 = 36x+6

Subtract 6 from each side

-18-6 = 36x+6-6

-24 = 36x

Divide by 36

-24/36 = 36x/36

Simplify

-2/3 = x

User Edelin
by
5.3k points